Cover Picture: Molecular Imaging of Biological Samples on Nanophotonic Laser Desorption Ionization Platforms (Angew. Chem. Int. Ed. 14/2016). Issue 14 (11th March 2016) - Stopka, Sylwia A.; Rong, Charles; Korte, Andrew R.; Yadavilli, Sridevi; Nazarian, Javad; Razunguzwa, Trust T.; Morris, Nicholas J.; Vertes, Akos
Abstract : Molecular tissue imaging by mass spectrometry is achieved by using nanostructured substrates. In their Communication onpage 4482 ff., A. Vertes and co‐workers show how laser desorption ionization from silicon nanopost arrays (NAPA) unlocks the metabolite and lipid distributions in biological tissues. The picture shows the laser pulse interacting with a mouse kidney tissue section and the underlying nanostructure to produce ions for mass spectrometry imaging (MSI).